MENIMBANG KEMBALI ‘KEADILAN’ PERJANJIAN KERJA MENGENAI UPAH MINIMUM PROVINSI (UMP) DAN IMPLIKASINYA TERHADAP LAW ENFORCEMENT DI INDONESIA (Pendekatan al-Siyasah al-Syar’iyyah) - Azizah, Ninik (Irtifaq, 2014)
The rights of workers receivedserious attention from thegovernment with the issuance ofLaw 13 of 2003 on Manpower.Publication of the JointMinisterial Decree (SKB) 4minister disturbing workers forlaw enforcement in Indonesia. Thisstudy shows that (1) the UMP(Provincial Minimum Wage) relatedpolicy shift for labor / worker byrising SKB 4 minister has violatedthe basic philosophy ofIndonesia's economic development(2) This policy shift is also notin accordance with maslahah al-'ammah, due to non-fulfillmentaspect of social justice law andjustice (3) a need for betterlegal protection for workers inthe form of the establishment ofpreventive and enforcement oflegislation and attempts toinstitutionalize the substantive